Conjunctive schedules of reinforcement: III. A fixed-interval adjusting fixed-ratio schedule - Barrett, James E. (1976)
Key pecking of three pigeons was studied under a conjunctive schedule that specified both a fixed-interval and an adjusting fixed-ratio requirement. The fixed-interval schedule was 6 min for one pigeon and 3 min for the other two. The size of the ratio requirement was determined within each cycle of the fixed interval by the duration of the pause before responding began. The fixed-ratio value was at maximum at the start of each fixed interval and decreased linearly until the first response occurred (adjusting fixed-ratio schedule). A peck produced food when the number of responses remaining on the fixed-ratio schedule was completed and when the fixed interval had elapsed. If no response occurred during the interval, the fixed-ratio requirement decreased to one and a single response after the interval elapsed produced food. The initial value of the adjusting fixed-ratio schedule was studied over a range of 0 to 900. Increases in the adjusting fixed-ratio schedule to about 300 responses increased both pause duration and running response rate and also modified the pattern of responding from that obtained under the fixed-interval schedule. Higher values of the adjusting fixed ratio generally decreased pause duration and running response rate and also disrupted responding. Interreinforcement time under the conjunctive schedule was increased substantially when the adjusting fixed-ratio size exceeded 300 responses.